The Use Of Pantule Media In Improving The Understanding Of Braille Hijaiyah For The Blind Group In SLBN Sampang - Isnaeni, Nur; Maghfiroh, Muliatul (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
Pantule media is the most basic media blind students use to practice reading and writing letter skills. The letters used by blind children are Braille. In this learning activity, the blind child only learns to read and write the alphabet and his PAI learning still includes material memorizing the pillars of Islam, the pillars of faith, the names of angels, the names of prophets and apostles, memorizing short surahs and memorizing daily prayers. Therefore, the author took the initiative to research the use of pantule media in increasing the understanding of the Braille Hijaiyah script for the blind group at SLBN Sampang. The aim is to introduce the Hijaiyah script while improving fluency in reading and writing Braille-based Hijaiyah so that students not only memorize the verses of the Al-Qur’an but are also able to know the Hijaiyah writing form. The approach used is through classroom action research (PTK) with the subject being a blind student. The model used follows the Kemmis & Mc. Taggart includes planning, action, observing, and reflection. The data analysis uses quantitative and qualitative data analysis with a classical success indicator of 85%. The results of the research obtained a pre-cycle average of 20 with a percentage of 0%, a cycle 1 average of 25 with a percentage of 0%, a cycle 2 average of 30 with a percentage of 0%, and a cycle 3 average of 35 with a percentage of 100%.   Keywords: Hijaiyah Script, Braille, Reflective Media, Blind.